Phenolic compounds in Nordic berry species and their application as potential natural food preservatives - Tian Ye; Yang Baoru (Taylor & Francis, 2022)
An increasing demand for natural food preservatives is raised by consumers. For Nordic berry species, abundance of phenolic compounds and potent activities of anti-oxidation and anti-bacteria enables a great potential as food preservatives. This review provides a systematic examination of current literature on phenolic profiles, anti-oxidative and anti-bacterial activities of various extracts of Nordic berry species, as well as the impact of various structure features of phenolics on the bioactivities. Special attention is placed on exploitation of leaves of berry species and pomaces after juice-pressing as side-streams of berry production and processing. The current progress and challenges in application of Nordic berry species as food preservatives are discussed. To fully explore the potential application of Nordic berry species in food industry and especially to valorize the side-streams of berry cultivation (leaves) and juice-pressing industry (pomaces), it is crucial to obtain extracts and fractions with targeted phenolic composition, which have high food preserving efficacy and minimal impact on sensory qualities of food products.